Особливості застосування хмарних технологій в навчальному процесі - Переверзєв, Антон Миколайович; Скляренко, Олена Вікторівна (НТУ "ХПІ", 2018)
Розглянуто можливості, переваги та недоліки застосування хмарних технологій в начальному процесі вищих навчальних закладів. Проведено короткий огляд основних постачальників сучасних освітніх платформ на основі використання хмарних технологій. Представлено сучасні програмні рішення та їх можливості, що можуть бути використані в організації навчального процесу.

Educational institutions should ensure the full development of the individual, for today it is impossible without using of the latest means of Internet communication. Cloud computing technologies implements of various forms of electronic, distance and mixed learning, and have significant advantages over traditional forms of education. The main purpose of this article is to explore the possibilities, advantages, and disadvantages of using cloud applications in the learning process of hi gher educational institutions. The review of the main suppliers of modern educational platforms based on using of cloud technologies is conducted, namely Microsoft, Amazon, Google, and IBM. Modern software solutions and their possibilities that can be used in the organization of educational processes are presented. Virtual learning environments are easy to use and do not require users to have deep knowledge of multimedia or communications tools or knowledge of programming languages. The opportunities of cloud technologies used in learning organization can have a significant impact on the formation of training tasks, assessment systems, and the final learning experience. Using of cloud technologies in the educational process will, above all, solve the problem of ensuring equal access of students and teachers to quality educational resources, regardless of their financial status, nationality, place of residence and state of health. In addition, using of cloud technologies in educational organizations will enable not only to improve the efficiency of the educational process and the convenience for teachers and students but also reduce economic costs. Cloud computing technologies enable students across the globe to acquire the 21st-century skills and training they need to compete and succeed in the global information society.
Features of application of cloud technologies in educational process
Keywords: хмарні обчислення; освітні платформи; вищі навчальні заклади; ВНЗ; програмне забезпечення; ПЗ; засоби масової інформації; cloud computing; educational platforms